Aspartate Aminotransferase to Platelet Ratio Index Score in Correlation with Neutrophil-to-Lymphocyte Ratio and Platelet-to-Lymphocyte Ratio to Predict Hepatic Cirrhosis in Hepatitis C Patients - Jane Haryanto; Agnes Rengga Indrati; Tiene Rostini (Faculty of Medicine Universitas Padjadjaran, 2022)
Background: Tissue biopsy examination which is an invasive procedure has become the mainstay for hepatic cirrhosis identification in patients with hepatitis. Alternatively, noninvasive method using the aspartate aminotransferase (AST) to platelet ratio index (APRI) score has been developed to predict hepatic cirrhosis. Furthermore, the neutrophil lymphocyte ratio (NLR) and platelet lymphocyte ratio (PLR) have been used to predict the severity of hepatitis C. This study aimed to analyze the relationship between APRI scores and NLR and PLR in chronic hepatitis C patients.Methods: This correlative cross-sectional observational study used secondary data of complete blood counts such as neutrophil, lymphocyte, and platelet values, as well as AST values of patients with hepatitis C in the outpatient and inpatient installation of Dr. Hasan Sadikin General Hospital during 2019. The inclusion criteria were patients aged ≥18 years, male and female, who were diagnosed as hepatitis C patients, patients who had AST examination data, leukocytes, count type, and platelets. Data were analyzed using the Spearman rank correlation test.Results: The 123 subjects were dominantly male with an age range of 46–55 years. There was no correlation between the APRI and NLR scores (p=0.229). However, there was a moderate and significant negative correlation between APRI and PLR scores with a correlation coefficient of -0.468 (p=0.000).Conclusion: There is a significant negative correlation between APRI and PLR scores to predict the occurrence of hepatic cirrhosis in patients with Hepatitis C.